OCCUPATIONAL SEDENTARY BEHAVIOR AND SOLUTIONS TO INCREASE NON-EXERCISE ACTIVITY THERMOGENESIS - Haley M. Scott; Tess N. Tyton; Craig A. Horswill (Universidad de Costa Rica, 2016)
As the prevalence of obesity rises worldwide, researchers pursue explanations for the phenomenon, particularly those relevant to energy expenditure.Non-exercise activity thermogenesis, or NEAT, has been identified as an inconspicuousbut appreciable component of total daily energy expenditure.Demands of certain occupations discourage time for planned physical activity and clearly diminish NEAT, and thereby contribute to sedentary behaviors thatunderlie increased adiposity. Prolonged sitting during the workday has specifically been identified as a risk factor for obesity and chronic disease independent of existing risk factors. Practical strategies have been launched by industry to increase NEAT during the workday.Workstations that involve maintaining balance while sitting on anexercise ball, standing, pedaling while sitting, and walking at a treadmill desk have been developed to counter extended periods of sedentary behavior at work.While data are limited particularly for chronic benefits, the stations that promote the most movement -the pedaling and walking stations -increase METS and energy expenditure more so than the other alternatives.The drawback to greater motion may be reduced attention to the desk job and therefore,reduced cognitive function; however, the data are inconsistent andthe benefit for health may outweigh small distractions for some tasks at the desk.